High power impulse magnetron sputtering of Zn/Al target in an Ar and Ar/O2 atmosphere: The study of sputtering process and AZO films - Zubkins, Martins; Arslan, H.; Bikse, Liga; Purans, Juris (Elsevier B.V., 2019)
Reactive high power impulse magnetron sputtering (R-HiPIMS) has been demonstrated as a promising technique for the ZnO:Al (AZO) thin film deposition at low temperature with improved electrical properties compared to the reactive direct current magnetron sputtering (R-dcMS). However, there are not enough studies about the HiPIMS process using Zn/Al target itself. Additionally, AZO films have not been deposited with the pulse duration times long enough to allow the discharge to develop into the self-sputtering mode. C-V-t characteristics and the time average plasma optical emission spectra were studied as a function of different sputtering parameters, such as frequency, average power, pulse duration time, and oxygen flow rate. AZO films were deposited on glass substrates without intentional heating by R-HiPIMS using 500 μs long pulses. Structural, electrical and optical properties of the AZO films were studied as a function of peak current. Obtained peak power densities are relatively low compared to other metals due to the strong argon gas rarefaction, however, it is possible to increase the peak power density above 0.5 kW/cm2 by increasing the time between pulses or the average power to reach the HiPIMS regime. If the pulse duration time is 500 μs, the sustained self-sputtering discharge can be observed when the peak power density is above 0.3 kW/cm2. The peak current is sensitive to the oxygen content in the sputtering atmosphere so that it can be used as a control parameter for the reactive sputtering. The lowest obtained resistivity of the AZO films is 1.0 × 10−3 Ωcm with the transmittance around 70% in the visible light range. From the XRD measurements, there is the indication of existing zincblende structural phase in the R-HiPIMS deposited AZO films using high oxygen partial pressure.
Financial support provided by Scientiﬁc Research Project for Students and Young Researchers Nr. SJZ/2017/4 realised at the Institute of Solid State Physics, University of Latvia is greatly acknowledged.
Keywords: Research Subject Categories::NATURAL SCIENCES:Physics; HiPIMS; Sustained self-sputtering; Reactive sputtering; ZnO:Al (AZO) films; Room temperature deposition